Yield and Biochemical Attributes of Brri Dhan-44 (Oryza Sativa L.) as Affected by Tiba Application - Adam, AMM Golam; Islam, Rasedul; Begum, Hasna Hena (Journal of the Asiatic Society of Bangladesh, Science, 2018)
A pot experiment was carried out to evaluate the effect of different concentrations (0, 10, 25, 50 and 100 ppm) of TIBA on yield and biochemical attributes of BRRI dhan-44. Results revealed that number of effective tillers and dry weight of panicle per plant, length of panicle, number of grains per panicle, 1000-grain weight, yield per plant and harvest index increased due to all concentrations of TIBA treatments where, treatments mean varied significantly in majority of cases. The stimulatory effect of TIBA treatments on number of effective tillers and dry weight of panicles per plant, length of panicle, number of grains per panicle and 1000-grain weight resulted significant increase in grain yield per plant. The maximum yield per plant (17.83 g) was obtained from 10 ppm TIBA treatment which was 59.76 % higher over the control. Increases in yield per plant due to 25, 50 and 100 ppm TIBA were 50.53, 47.58 and 28.49%, respectively. Findings of this investigation showed that foliar application of TIBA had beneficial effect on pigment content of leaves at tillering and grain filling stages with a few exceptions. Protein content of leaves was also positively influenced by most of the treatment at tillering stage. Out of five treatments, 10 ppm TIBA produced better results. Asiat. Soc. Bangladesh, Sci. 44(2): 117-125, December 2018